Penny and Pup - Linda Jennings & Jane Chapman
Penny the puppy has a toy all of her own. Pup is all squashy and floppy, and Penny chews and loves him to bits. Penny doesn't think he needs any other friends, but then one day Pup is lost and Penny doesn't know who to turn to for help.